PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA - Ian Nurpatria Suryawan; Richard Andrew (Universitas Trisakti, 2013)
Research is intended to test influence Motivation against Job Satisfaction work lecturer at Economics Faculty,